If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -13 = 2(3 + -1x) Reorder the terms: -13 + 4x = 2(3 + -1x) -13 + 4x = (3 * 2 + -1x * 2) -13 + 4x = (6 + -2x) Solving -13 + 4x = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -13 + 4x + 2x = 6 + -2x + 2x Combine like terms: 4x + 2x = 6x -13 + 6x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 -13 + 6x = 6 + 0 -13 + 6x = 6 Add '13' to each side of the equation. -13 + 13 + 6x = 6 + 13 Combine like terms: -13 + 13 = 0 0 + 6x = 6 + 13 6x = 6 + 13 Combine like terms: 6 + 13 = 19 6x = 19 Divide each side by '6'. x = 3.166666667 Simplifying x = 3.166666667
| 5w+27+4w=9 | | 8-2t=14+t | | 2(2y-1)+y=5(y+3) | | -9x+5(-3x-4)=-42-2x | | 40+40*0+1= | | 2x+7(3x-4)=-2-3x | | -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 | | 976x-x^2=213.495 | | 1/14=27/7*1/30 | | 10x-2y=5 | | -2x^2+17x-8=0 | | 6x-2y=1 | | -99=33y | | 8j-4k=4 | | 5(k-2)-6=5k-(4k-3) | | 3j+4k=23.5 | | 11f+10g=25 | | Y=150x+800 | | 22=-2+3s | | -2-19= | | 4m(4n-8)+6mn-2m= |